OROPHARYNGEAL CANCER MORTALITY ACCORDING TO THE HUMAN DEVELOPMENT INDEX IN THE METROPOLITAN REGION OF CHILE, 2002-2014 - Vicente Livacic; José Tomás Grez; Jorge Candia; Alejandra Fernandez (Universidad de Concepción., 2018)
To determine mortality rates for oropharyngeal cancer according to the Human Development Index (HDI) per district in the Metropolitan Region (RM), Santiago, Chile, between 2002 and 2014. Materials and Methods: An ecological study was carried out. The sample corresponded to individuals over 45 years, from the Metropolitan Region, with oropharyngeal cancer as cause of death, as registered in the Chilean National Institute of Statistics (INE). The HDI was classified into three categories: "medium" (8 districts), "high" (18 districts) and "very high" (25 districts). The crude and adjusted mortality rates were calculated for each year and period. Results: The oropharyngeal cancer adjusted mortality rate for the chosen period was 3.98 deaths per 100,000 inhabitants. The specific mortality rate from oropharyngeal cancer in the "medium" HDI category was 4.01; in the "high" DHI category, 4.42; and in the "very high" HDI category, 3.79. Conclusion: Mortality from oropharyngeal cancer was higher in the "medium" HDI category between 2002 and 2014.